MUSICIANS' COPING STRATEGIES AMID THE COVID-19 PANDEMIC - Simarmata, Marina; Tobing, David Hizkia (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The emergence of the COVID-19 pandemic added to the problems and obstacles faced by musicians. Enforcement of a policy of limiting activities makes all musicians becomes hampered. Problem such as job loss faced by musicians can cause stress. Applying the right coping strategies can help musicians make adjustments and avoid prolonged stress. This research aims to find out what coping strategies are used by the musicians lost amid the COVID-19 pandemic and what factors influence the choice of coping strategy by using qualitative methods phenomenological approach. Data collection using semi-structured interviews. Respondents in this study were 5 musicians who lost their jobs in the middle the COVID-19 pandemic and experiencing problems or obstacles at work as musicians due to the COVID-19 pandemic. The results show that the strategy method coping used by respondents consist of distraction, problem solving, and support seeking. The choice of coping strategy methods in this study is influenced by desire yourself, hobbies and abilities, as well as family and friendship environment. Impact that arises after carrying out coping strategies is to feel calm and happy and the economic situation is getting better as seen from the income of the respondents which increases.